Embedding Co in perovskite MoO3 for superior catalytic oxidation of refractory organic pollutants with peroxymonosulfate. (February 2023) - Zeng, Qingyi; Tan, Jing; Gao, Beibei; Cai, Tao; Zhang, Qingyan; Liu, Yi-Lin; Chang, Sheng; Zhao, Shuaifei; Wu, Suqing
Abstract: A cobalt (Co)-doped perovskite molybdenum trioxide (α-MoO3 ) catalyst (Co-MO) was synthesized by a facile pyrolysis strategy and used for degrading various organic contaminants via peroxymonosulfate (PMS) activation. The doped Co was inserted in the inter space between the octahedron [MoO6 ], facilitating the growth of the α-MoO3 crystal on the [010] direction. This unique structure accelerated the activation of PMS as the Co-MO could function as a carrier for electron transfer to facilitate the Co(II)/Co(III) cycle in the Co-MO/PMS system. As a result, the Co-MO/PMS system showed noticeable activity for removing 100% bisphenol A (BPA) under a broad conditions within 30 min. The radical quenching test and electron paramagnetic resonance analysis revealed that singlet oxygen ( 1 O2 ) was the main active species for BPA degradation in the Co-MO/PMS system, while free radicals, such as O2 -, SO4 - and OH, were also produced as the intermediate species. Furthermore, the carrier mechanism may enable the Co-MO/PMS system maintain relatively high performance during repeat use, and also excellent adaptability was revealed by the well function in various water matrices and high activity in degrading various refractory organic pollutants. Our findings pave a useful avenue for the rational design of novel cobalt-doped catalysts with high catalytic performance toward wide environmental applications. Graphical abstract: A perovskite Co-doped molybdenum trioxide catalyst was synthesized by a facile pyrolysis strategy and used for degrading various organic contaminants via peroxymonosulfate activation. Image 1 Highlights: A perovskite Co-MO catalyst was synthesized by a facile pyrolysis strategy. Effects of doping amount, annealing temperature and duration were studied systematically. Co-MO/PMS system noticeably removed 100% BPA under a broad conditions within 30 min. 1 O2 was the main active species under the activation of PMS by triggering the Co(II)/Co(III) cycle. The fantastic adaptability of the Co-MO/PMS system was also demonstrated.